The Influence of the Principal's Role on the Quality of Education in Madrasah Aliyah throughout Lasem District, Rembang Regency - Diyah Irnawati; Maryanto Maryanto; Ghufron Abdullah (Dinasti Publisher, 2025)
This study aims to analyze the influence of the principal's role on the quality of education in Madrasah Aliyah throughout Lasem District, Rembang Regency. Madrasahs play a strategic role in shaping academically and religiously outstanding generations; however, the quality of education in the region remains low. The study involved 101 teachers from three madrasahs using a quantitative approach and an ex post facto method. Data were collected through questionnaires measuring the variables of the principal's role and education quality. The analysis results indicate a positive and significant influence between the principal's role and education quality, with a correlation coefficient of 0.717 and a significance value of 0.000 in the ANOVA test. This suggests that the principal's role contributes 51.4% to improving education quality. The administrative role dimension was found to contribute the most, whereas the supervisory role has not been optimally implemented. These findings highlight the importance of effective educational leadership in enhancing the quality of education in madrasahs and the need for managerial strategies that can facilitate sustainable improvements in education quality.